2017
DOI: 10.1016/j.materresbull.2016.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric and dielectric study of strontium tantalum based perovskite oxynitride films deposited by reactive rf magnetron sputtering

Abstract: International audienceStrontium and tantalum based oxynitride perovskite thin films were deposited by reactive magnetron sputtering. Epitaxial films deposited on Nb-SrTiO3 substrates show smooth surfaces with roughness values from 1.5 to 3.6 nm for a thickness of films in the range 20–1600 nm. The samples are yellow with band gap values around 2.35 eV. Piezo-force microscopy characterization pointed out the local piezoelectric and ferroelectric behavior of the oxynitride perovskite films. In the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…We will compare our results to those obtained on standard ferroelectrics, for example Ba 1-x Sr x TiO 3 [3,4], as well as isotype layered perovskite systems such as (Sr,La) 2 (Ta,Nb) 2 O 7 ceramics [9] and Sr 2 (Ta 1-x Nb x ) 2 O 7 as single-crystals [10,11] and thin films [12][13][14]. The present work relies also on our previous studies concerning La 2 Ti 2 O 7 in the form of ceramics [15] and thin films [16] and our first attempt to produce directly STLT films [17].…”
Section: Introductionmentioning
confidence: 96%
“…We will compare our results to those obtained on standard ferroelectrics, for example Ba 1-x Sr x TiO 3 [3,4], as well as isotype layered perovskite systems such as (Sr,La) 2 (Ta,Nb) 2 O 7 ceramics [9] and Sr 2 (Ta 1-x Nb x ) 2 O 7 as single-crystals [10,11] and thin films [12][13][14]. The present work relies also on our previous studies concerning La 2 Ti 2 O 7 in the form of ceramics [15] and thin films [16] and our first attempt to produce directly STLT films [17].…”
Section: Introductionmentioning
confidence: 96%
“…For oxynitrides, the oxidation state of the cations, the bond covalence and the band structure can be tuned by mixing oxygen and nitrogen. The wide range of electronic and optical properties make them promising candidates for photocatalysis [1,2], electronic [3,4,5] and solar energy applications [6].…”
Section: Introductionmentioning
confidence: 99%
“…First-principles calculations suggested that compressive biaxial stress stabilizes the metastable ferroelectric trans structure relative to the most stable cis structure, and classical ferroelectric behavior was observed in tetragonally strained SrTaO 2 N epitaxial thin films grown on Nb:SrTiO 3 (NSTO) substrates. However, no experimental evidence for the trans -type anion configuration was obtained. , Neutron diffraction analysis, which has been used to determine the anion arrangements in bulk mixed-anion compounds, is not applicable to thin-film samples, because of their small volumes. Consequently, the concept of strain engineering for anion arrangement in mixed-anion compounds is still a controversial issue.…”
mentioning
confidence: 99%
“…However, no experimental evidence for the trans-type anion configuration was obtained. 16,17 Neutron diffraction analysis, which has been used to determine the anion arrangements in bulk mixed-anion compounds, is not applicable to thin-film samples, because of their small volumes. Consequently, the concept of strain engineering for anion arrangement in mixed-anion compounds is still a controversial issue.…”
mentioning
confidence: 99%